Conflitos nos relacionamentos de genitores em situação de disputa de guarda: uma contribuição para a compreensão da alienação parental - Silveira, Silvana Magayevski da (Universidade do Vale do Rio dos Sinos, 2013)
This thesis started from the finding that there is a need for a deeper study of child custody situations, especially regarding to assessment and intervention in situations which parental alienation is involved. It is divided into two articles. The first article is theoretical and introduces he terms parental alienation and parental alienation syndrome. It describes the behavior displayed by the parents involved in this type of conflictual relationship and reviews the discussions and Brazilian studies on this issue in order to contextualize this problem still little known and empirically studied. The second article is a multiple case study that aims to evaluate standard conflicts in relationships presented by parents involved in parental alienation, being 2 alienated and 2 alienating. The cases were collected and analyzed in accordance with the method CCRT (Core Conflictual Relationship Theme) by Lester Luborsky. Through interviews, a testimony about separation and current situation of participants was collected and an account of several interpersonal situations was obtained, which allowed obtaining the CCRT or central theme of conflict in relationships. The results indicate that the main desire of the people involved in the dynamics of parental alienation is to be loved and understood and that the loss of this love is a vulnerability factor.
Keywords: Divórcio; Alienação parental; Relacionamentos; Conflitos; Método CCRT; Divorce; Parental alienation; Relationships; Conflicts; CCRT method; ACCNPQ::Ciências Humanas::Psicologia